Population Ecology And The Habitat Suitability Of Norway Rat (Rattus Norvegicus) In Selected Urban Areas Of Penang, Malaysia - Khairuddin, Nurul Liyana (2013)
A study regarding the population ecology and prediction on habitat suitability of Norway rat (Rattus norvegicus) was carried out in selected urban areas of Georgetown, Penang. The study areas involve three major settlement areas; inner city area (Site A), mixed settlement area (Site B) and commercial area (Site C). In the population study, 42 trapping locations were selected in three major settlement areas, with each area constituent 14 trapping locations. A total of 786 individual rats were caught in 10 months sampling period, with R. norvegicus was the dominant rat species; 748 individuals. Inner city area shows the highest captured of 321 rats followed by mixed settlement area and commercial area; 306 rats and 159 rats respectively. Study concerning the bait selection for rat capture shows peanut butter with bread was the best choice of bait c2( 3, N=163) = 13.04, p < 0.05. The distribution of R. norvegicus in Georgetown is not evenly distributed but in patches. Adult male and adult female show small home range size and the movement is limited between nest and food location. R. norvegicus was confirmed to be active during early night towards mid nights, 2100 - 2300 hours and 0300 - 0400 hours. Habitat suitability map has the ability to identify and predict area with high degree of infestation. The map was validated using an independent set of trapping data.